(501) The Seasonal Employment Profile in Egyptian Agriculture الملف الموسمي للتوظيف في الزراعة المصرية - El Tomy, Mona; Hensen, Bent (INP, 2024)
This study examines seasonal employment patterns in Egyptian agriculture as a major topic in labor economics and agricultural development. The study aims to analyze seasonal fluctuations in agricultural labor demand and to assess the extent of underemployment and disguised unemployment within the agricultural sector. It is based on a revised and expanded version of earlier labor requirement estimates prepared by the Ministry of Agriculture, while attempting to address methodological and statistical limitations in previous calculations. The study begins by defining major concepts related to agricultural labor markets, including open unemployment, disguised unemployment, and underemployment. Open unemployment refers to individuals willing but unable to obtain work, while disguised unemployment refers to labor that can be withdrawn without reducing output. Underemployment describes situations in which farm workers or family members do not obtain full employment throughout the agricultural year. The study also distinguishes between seasonal and permanent forms of each category. Methodologically, the analysis relies on agricultural census data and labor requirements associated with major crops. Monthly labor requirements per person within the permanent agricultural labor force were estimated. Labor was classified into two groups: men and women with children, and separate as well as combined analyses were conducted. The findings reveal strong seasonal fluctuations in agricultural labor demand, with seasonality appearing more pronounced among women and children than among men. Labor demand for men reached a peak during May, whereas women and children experienced two major peaks during June and September because of rice planting, cotton pest control activities, and cotton harvesting operations. The findings provide little evidence of significant permanent underemployment; instead, labor demand during peak periods occasionally exceeded the available permanent labor force and required additional seasonal labor. The study concludes that agricultural employment problems in Egypt are primarily associated with seasonal labor fluctuations rather than with a permanent labor surplus, emphasizing the need for development policies capable of creating complementary employment opportunities during seasonal low-activity periods.